Predation of a Buff-banded Rail'Hypotaenidia philippensis' by Australian Ravens' Corvus coronoides' on Penguin Island, Western Australia - Barr, James (BirdLife Australia, 2019)
Australian Ravens Corvus coronoides, although primarily scavengers, are known to prey on large vertebrates, which can detrimentally affect the prey populations. This paper describes an Australian Raven attacking and killing a Buffbanded Rail Hypotaenidia philippensis on Penguin Island, Western Australia, in the presence of several other Ravens.